Influence of maternal lipid levels on adverse pregnancy outcomes in women with gestational diabetes mellitus - Ru Zhao; Ru Zhao; Jun Hu; Yuanqin Li; Yuanqin Li; Xuetao Chen; Xuetao Chen; Qian Wang; Qian Wang; Tingting Wu; Tingting Wu; Weihong Zhou; et al. (Frontiers in Endocrinology)
ObjectiveThis study aimed to investigate the effect of mid-pregnancy lipid levels on adverse outcomes in women with gestational diabetes mellitus (GDM) under adequate glycemic control. Whether this effect is independent of factors such as blood glucose was also analyzed.MethodsWe retrospectively analyzed 1,001 women with normal glucose tolerance (NGT) and 1,078 women with GDM under adequate glycemic control from 2015 to 2024. Logistic regression analysis was used to explore the relationship between blood lipids and adverse outcomes. Those with GDM were further classified according to their pre-pregnancy body mass index (BMI), gestational weight gain, glycosylated hemoglobin A1c (HbA1c), and fasting blood glucose (FBG). An interaction model between triglyceride (TG) and pre-pregnancy BMI, gestational weight gain, HbA1c, and FBG on adverse outcomes was constructed.ResultsIn GDM, high levels of TG were independent risk factors for preeclampsia (OR = 1.51, 95%CI = 1.18–1.93), preterm birth (OR = 1.68, 95%CI = 1.30–2.18), macrosomia (OR = 1.48, 95%CI = 1.14–1.92), postpartum hemorrhage (OR = 1.33, 95%CI = 1.10–1.61), and intrauterine fetal distress (OR = 1.68, 95%CI = 1.13–2.51). Furthermore, TG had a greater impact on GDM women than on NGT women. In addition, in GDM, high levels of TG were independent risk factors for the above adverse outcomes in the subgroups of pre-pregnancy BMI, gestational weight gain, HbA1c, and FBG (interaction p > 0.05).ConclusionsHigh levels of TG promoted the occurrence of preeclampsia, preterm birth, macrosomia, postpartum hemorrhage, and intrauterine fetal distress in women with GDM. Furthermore, TG had a greater effect on adverse outcomes in GDM than in NGT women.